Identification of biomarkers and outcomes of endocrine disruption in human ovarian cortex using In Vitro Models. (February 2023) - Li, Tianyi; Vazakidou, Paraskevi; Leonards, Pim E.G.; Damdimopoulos, Anastasios; Panagiotou, Eleftheria Maria; Arnelo, Catarina; Jansson, Kerstin; Pettersson, Karin; Papaikonomou, Kiriaki; van Duursen, Majorie; Damdimopoulou, Pauliina
Abstract: Endocrine disrupting chemicals (EDCs) are raising concerns about adverse effects on fertility in women. However, there is a lack of information regarding mechanisms and effects in humans. Our study aims to identify mechanisms of endocrine disruption using two EDCs, diethylstilbestrol (DES) and ketoconazole (KTZ) 1 . Human ovarian cortical tissue obtained from Caesarean section patients was exposed to 10 −9 M - 10 −5 M KTZ and 10 −10 M - 10 −6 M DES in vitro for 6 days. Follicle survival and growth were studied via histology analysis and liquid-chromatography-mass spectrometry-based steroid quantification. RNA-sequencing was performed on COV434, KGN, and primary ovarian cells that were exposed for 24 h. Significantly lower unilaminar follicle densities were observed in DES 10 −10 M group, whereas low KTZ exposure reduced secondary follicle density. KTZ 10 −5 M reduced levels of pregnenolone and progesterone. RNA-sequencing revealed that 445 and 233 differentially expressed genes (false discovery rate < 0.1) altogether in DES and KTZ exposed groups. Gene set variation analysis showed that both chemicals modulated pathways that are important for folliculogenesis and steroidogenesis. We selected stearoyl-CoA desaturase ( SCD ) and 7-dehydrocholesterol reductase ( DHCR7 ) for further validation. Up-regulation of both genes in response to KTZ was confirmed by qPCR and in situ RNA hybridization. Further validation with immunofluorescence focused on the expression of SCD in growing follicles in exposed ovarian tissue. In conclusion, SCD may serve as a potential novel human-relevant biomarker of EDC exposure and effects on ovaries.